2018
DOI: 10.1002/wene.290
|View full text |Cite
|
Sign up to set email alerts
|

Smart grid governance: An international review of evolving policy issues and innovations

Abstract: The electric power systems of many industrialized nations are challenged by the need to accommodate distributed renewable generation, increasing demands of a digital society, growing threats to infrastructure security, and concerns over global climate disruption. The “smart grid”—with a two‐way flow of electricity and information between utilities and consumers—can help address these challenges, but various financial, regulatory, and technical obstacles hinder its rapid deployment. An overview of experiences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…74 Turton et al classify possible V2G services in terms of peak power, spinning reserves, or regulation services; 75 Han and Han emphasize the V2G benefits of frequency regulation and spinning reserves, especially when optimized to charge batteries during offpeak periods, and to then feed power into the grid during expensive peak periods. 76 Source: 78 Our data however is more critical and discriminating as to which types of such services would be best suited for V2G. R83 for instance strongly argues that only frequency balancing is valuable:…”
Section: Vehicle Ownersmentioning
confidence: 99%
See 1 more Smart Citation
“…74 Turton et al classify possible V2G services in terms of peak power, spinning reserves, or regulation services; 75 Han and Han emphasize the V2G benefits of frequency regulation and spinning reserves, especially when optimized to charge batteries during offpeak periods, and to then feed power into the grid during expensive peak periods. 76 Source: 78 Our data however is more critical and discriminating as to which types of such services would be best suited for V2G. R83 for instance strongly argues that only frequency balancing is valuable:…”
Section: Vehicle Ownersmentioning
confidence: 99%
“…Brown et al. lastly divide possible grid services from EVs across Grid-to-Vehicle, Vehicle-to-Buildings, and Vehicle-to-Grid platforms shown in Figure3 77. …”
mentioning
confidence: 99%
“…Hybrid heating systems are generally accepted by households, especially when they consist of a supplementary heating source added to a main heating source (Ruokamo, 2016).However, there are a number of challenges facing consumer load management. One of these challenges can be the consumer price, which is calculated based on an average power price and hence, does not incentivize the consumers to offer their load flexibility to the grid (Brown et al, 2018). Bergaentzlé, Jensen, Skytte, and Olsen (2019) studied the effect of alternative tariff schemes, such as ToU electricity tariffs on the flexibility and cost optimization of district heating plants and showed that ToU tariffs incentivize flexible power consumption in the district heating sector and reduce the overall heating costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Danish state aims to be fully independent from fossil fuels by 2050 (Danish Energy Agency, 2015). A renewable based energy system consists of many volatile power resources such as wind and solar energy that present new challenges for the energy system (Brown, Zhou, & Ahmadi, 2018). The emergence of flexible energy loads and producers is thus crucial to reach this objective by 2050 (Söder et al, 2018;Tuohy, Kaun, & Entriken, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The uneven geographic distribution of wind and solar potential is likely to burden the grid at some sites, resulting in transmission and distribution restrictions. Some electricity markets, such as the California Independent System Operator (CAISO) in Germany and the United Kingdom, have begun to recognize variable and resilient electrical resources to varying degrees [69,70]. In addition, the Federal Energy Regulatory Commission (FERC) and Pennsylvania-New Jersey-Maryland (PJM) Interconnection policy makers in the United States are also shifting their focus to the role that battery energy storage and flexible resources such as distributed resource aggregators (DRAs) play in the development of electricity markets [71].…”
Section: Literature Reviewmentioning
confidence: 99%